Antimicrobial Efficacy of Punica granatum mesocarp, Nelumbo nucifera Leaf, Psidium guajava Leaf and Coffea Canephora Extract on Common Oral Pathogens: An In-vitro Study - Mehta, Viral V. (JCDR Research and Publications (P) Limited, 2014)
Background and Objectives: Alternative therapies are increasingly being explored as extensive use of synthetic chemicals has led to the emergence of substantial side effects. Phytomedicine has been well practiced as traditional medicine in various cultures for treatment of oral diseases. It has gained importance of late as an alternative to the conventional therapy. Various plant and fruit extracts have been monitored recently to assess their potential against the common oral pathogens. Aim of this study was to assess in-vitro efficacy of pomegranate peel, lotus leaf, guava leaf and coffee extracts on oral microorganisms. Materials and Methods: Concentrations of 1%, 5%, 10%, 15% and 20% were prepared for each, followed by efficacy testing using disc diffusion method against Streptococcus mutans, Streptococcus mitis, Porphyromonas gingivalis, Prevotella intermedia and Candida albicans. Results: All the four extracts were found to be effective against S.mutans and S.mitis, with maximum efficacy against S.mutans and S.mitis displayed by pomegranate and lotus. Antifungal efficacy was demonstrated by coffee and pomegranate. Guava, lotus and coffee were effective against P.intermedia, while only coffee was found to be effective against P. gingivalis. All the results were found to be statistically significant (p < 0.05). Interpretation & Conclusion: Pomegranate, guava, lotus and coffee displayed significant anticariogenic effect while coffee was found to be most effective against periodontal pathogens as well as Candida albicans. Results revealed that natural products may be used as economical and suitable adjuvant to synthetic medicines and compounds and their judicious use might not only help to inhibit the side effects of synthetic chemicals but also prove to be cost effective in developing economies.